Clinical importance of immunonutrition in infants: a review of the recent literature - Ji Sook Park (The Korean Pediatric Society, 2022)
During the last decades, the role of nutrition has been well elucidated in medicine, especially among critically ill infants and children. Many nutrients have the potential to modulate the immune system. A healthy immune system is essential for the prevention and recovery of many pediatric illnesses. Intervention using specific nutrients for the immune system is called immunonutrition. Immunonutrient supplementation has been attempted to modulate inflammatory or immune responses, leading to an improved clinical course of critically ill patients with prolonged nutritional supplementation parenterally or enterally. This review discusses immunomodulatory nutrients for infants based on the recent literature.